Cerebral aspergillosis after heart-lung transplantation in a child: Case report with 3-year follow-up and literature review - Zhuang, Huanwei; Xiang, Kun; Gong, Shuji; Zhou, Yangang; Chen, Jinlan (Frontiers in Cardiovascular Medicine, 2023)
There are limited cases of heart-lung transplantation (HLT) in children worldwide owing to lack of donors, demanding surgical teamwork, and arduous post-operative management. Post-transplant management difficulties stem from the possible development of several post-operative complications, with infection being a common complication. Intracranial fungal infections are difficult to diagnose and prone to treatment delays because of their relatively insidious onset and atypical clinical presentation. Here, we present a case of a cerebral infection developed 3 months after HLT in a 10-year-old child, showing no positive results on conventional imaging or cerebrospinal fluid (CSF) examination and culture. On metagenomic next-generation sequencing of the cerebrospinal fluid, the causative organism was finally determined as Aspergillus. After administering 1-year anti-Aspergillus treatment, no recurrence of intracranial fungal infection was noted during the 3-year follow-up. This case illustrates the multifaceted diagnostic techniques for cerebral aspergillosis after HLT and shows the significance of dynamic monitoring of symptoms, such as headache, and of metagenomic sequencing results, trends in intracranial pressure and (1-3)-β-D-glucan levels for guiding diagnosis and treatment.